Determining Molecular-Level Interactions of Carboxyl-Functionalized Nanodiamonds with Bacterial Membrane Models as the Basis for Antimicrobial Activity - Sousa, Giovanna Eller Silva [UNESP]; Martins, Bruna Alves [UNESP]; Mendes de Almeida Junior, Alexandre [UNESP]; Queiroz, Rafaela Campos; Tada, Dayane Batista; Camacho, Sabrina Aléssio [UNESP]; Oliveira, Osvaldo N.; Aoki, Pedro Henrique Benites [UNESP] (American Chemical Society (ACS), 2025)
Carbon-based nanostructures, such as carboxylated nanodiamonds (NDCOOHs), are promising to combat resistant bacterial strains by targeting their protective membranes. Understanding their interactions with bacterial membranes is therefore important for elucidating the mechanisms underlying NDCOOHs antimicrobial activity. In this study, we investigated the incorporation of NDCOOHs into lipid Langmuir monolayers mimicking cytoplasmic membranes of Escherichia coli and Staphylococcus aureus, model systems for Gram-negative and Gram-positive bacteria, respectively. Using polarization-modulated infrared reflection-absorption spectroscopy (PM-IRRAS), we observed significant interactions between NDCOOHs and the polar head groups of the E. coli lipid monolayer, driven by electrostatic attraction to ammonium groups and repulsion from phosphate and carbonyl ester groups, limiting deeper penetration into the lipid chains. In contrast, S. aureus monolayers exhibited more pronounced changes in their hydrocarbon chains, indicating deeper NDCOOHs penetration. NDCOOHs incorporation increased the surface area of the E. coli monolayer by approximately 4% and reduced that of S. aureus by about 8%, changes likely attributed to lipid oxidation induced by superoxide and/or hydroxyl radicals generated by NDCOOHs. These findings highlight the distinct interactions of NDCOOHs with Gram-positive and Gram-negative lipid membranes, offering valuable insights for their development as targeted antimicrobial agents.